Investigating risk contagion initiated by endogenous liquidity shocks: evidence from the US and eurozone interbank markets. Issue 1 (2nd January 2019) - Eross, Andrea; Urquhart, Andrew; Wolfe, Simon
ABSTRACT: This paper investigates liquidity spillovers between the US and European interbank markets during turbulent and tranquil periods. We show that an endogenous model with time-varying transition probabilities is effective in describing the propagation of liquidity shocks within the interbank market, while predicting liquidity crashes characterised by changed dynamics. We show that liquidity shocks, originating from movements of the spread between the Asset Backed Commercial Paper and T-bill, drive regime changes in the euro fixed-float OIS swap rate. Our results support the idea of endogenous contagion from the US money market to the eurozone money market during the global financial crisis.